Evaluation of xylano-pectinolytic enzymes and oil palm empty fruit bunch pulp biobleaching by local isolate of Bacillus spp. - Mohd Nawawi, Muhammad Hariadi (2021)
The growing public concern about the environment in the pulp and paper industry has resulted in an increase demand of technological changes in the bleaching processes. The use of combined xylanase and pectinase in pulp bleaching could assist in enhancing the brightness of paper and reduce harmful chemical and pectins produced in the effluent and thus, rendering a more eco-friendly papermaking process, as well as improvements in the paper quality. The aim of this research was to study the production and characterisation of xylano-pectinolytic enzymes from a bacterial isolate Bacillus amyloliquefaciens ADI2 and to examine the effectiveness of using xylano-pectinolytic enzymes on OPEFB pulp in biobleaching. Bacillus amyloliquefaciens ADI2, as the potentially high extracellular xylanase and pectinase producer, which was isolated out of 86 isolates, from composting and rotting areas around Selayang in Selangor, Malaysia. RSM analysis demonstrated the optimum pH and temperature for xylano-pectinolytic enzymes production by Bacillus amyloliquefaciens ADI2 was at pH 8.38 and 28°C. Optimum inoculum size was at 4% (v/v) and agitation speed of 94 rpm with banana peel as the best substrate. Bacillus amyloliquefaciens ADI2 is an alkalophilic thermotolerant bacterium which under optimal cultural conditions, can produce 1.34 times more xylanase and 5.96 times more pectinase than prior to the optimisation study (OFAT). Xylano-pectinolytic enzymes were successfully purified with the recovery of 33.45% and 47.86% for xylanase and pectinase, respectively, weighing around 11 kDa (xylanase) and 31 kDa (pectinase). Xylanase and pectinase were also regarded to be active in broad ranges of pH particularly in alkaline conditions (pH 7.5-10) and being thermally active in the near thermophilic state (40-50°C), enzyme production can be further increased by the addition of Ca2+. Xylanase activity was enhanced by EDTA, glycine, and T-80, while no stimulation of activity was observed for pectinase. These enzymes also exhibited high binding affinities (Km) towards xylan beechwood (1.48 mg/mL - xylanase) and polygalacturonic acid (0.96 mg/mL - pectinase). Optimal enzymatic processes for pretreatment of biobleaching were studied, in which the xylanase-pectinase doses required were 15 and 19.2 U/g of oven dried pulp, and the effective retention time needed for pretreatment was 180 min. The recommended pH for pretreatment and temperature were pH 8.5 and 40°C, respectively. In the D1EpD2 process, the optimised enzymatic processes significantly improved the pulp properties and showed that the kappa number decreased from 122.8 (control) to 89.5 (treated) compared to 100.8 (untreated). Furthermore, the treated handsheet showed 11.25% enhancement in brightness with 28% compared to the untreated handsheet with 24.85%, which subsequently resulted in an 11.25% reduction of chlorine or chemical consumption. On the other hand, treated OPEFB pulp improved the quality of paper, where there were gains of 30% in tensile strength, 19.4% in bursting index, 20.9% in tearing index contrasted to conventional bleaching. In conclusion, xylano-pectinolytic enzymes from Bacillus amyloliquefaciens ADI2 showed interesting biotechnological characteristics that are suitable for application in the pulp and paper industry.